Good Governance dalam Perspektif Hukum Islam (Studi Kajian Ilmu Ushul Fiqh) - Muhammad Islahuddin (Asy-Syari’ah : Jurnal Hukum Islam, 2020)
The concept of good governance in a review of Islamic law is more directed at how to utilize the methods offered in the science of Jurisprudence to formulate the principles of Islamic law to respond to various problems that occur in government. The many problems that occur in government governance, therefore we are required to examine the reality of the current state of government to be better, professional, responsible, trustworthy. One of them is by building the concept of good governance in the hope of contributing to the development of better bureaucratic governance in accordance with the principles and values in Islamic law, such as the value of equality, tasamuh (tolerance), justice (justice), benefit, deliberation (shura), honesty (honesty), objective (comprehensiveness) and this is an indication of the formation of clean and good governance (good and clean governance). The approach used is the Usul Fiqh approach as a philosophical foundation in Islamic law by describing the new theory of Fiqh as the application of theory (applied theory) in exploring the values leading to public service. In other terms it can be called clean governance in the perspective of Islamic law.